(untitled) (Research, Society and Development, 2025)
Objective: This study aimed to investigate the perspective of parents/caregivers of children with Autism Spectrum Disorder (ASD) in the city of Divinópolis, MG, Brazil, regarding the treatments and follow-up that their children receive. Methodology: Qualitative descriptive study with parents and caregivers of children with ASD. Data were analyzed according to Bardin’s content analysis methodology. Results: Data were categorized into 4 central themes: symptoms, well-being, treatments, and general support. The common manifestations of parents/caregivers were mainly related to the beneficial effects of therapies and medications on the well-being of children, the notable reduction of negative behaviors, improvement in sleep quality, and correction of food selectivity. School emerged as an important factor of support, as well as the support of friends. The lack of specialized services in the SUS, financial difficulties, and the high cost of therapies were also critical points reported by participants. Conclusion: This study allowed us to give a voice to parents/caregivers of children with ASD, finding positive and negative points in common in the perspective of these actors in relation to the treatment that children receive in the municipality.